2021
DOI: 10.1521/pedi_2021_35_518
|View full text |Cite
|
Sign up to set email alerts
|

Interpersonal Problems in Parents and Adolescent Borderline Personality Disorder Features

Abstract: Research shows that parental personality pathology is associated with borderline personality disorder features and internalizing/externalizing symptoms in offspring. However, studies have been limited by DSM-IV–based assessments of parental personality pathology. The authors leveraged evidence that interpersonal problems described by the Interpersonal Circumplex align with Criterion A of the DSM-5 Alternative Model for Personality Disorders and therefore used a measure of interpersonal problems to capture pare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 65 publications
1
3
0
Order By: Relevance
“…Additionally, unlike the secure vs. insecure classification, previous research has failed to find associations between the CAI disorganized attachment classification and self-report measures of attachment in adolescents [66], raising questions about this dichotomous rating scale during adolescence. These findings align with previous IPC research showing associations between interpersonal problems and maladaptive attachment in adult close relationships [22] and add to only one existing study on the intergenerational risk associated with parental interpersonal problems [28], which found that parental interpersonal problems were associated with adolescent BPD features. This is the first study to suggest a relationship between maternal interpersonal problems and offspring attachment.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Additionally, unlike the secure vs. insecure classification, previous research has failed to find associations between the CAI disorganized attachment classification and self-report measures of attachment in adolescents [66], raising questions about this dichotomous rating scale during adolescence. These findings align with previous IPC research showing associations between interpersonal problems and maladaptive attachment in adult close relationships [22] and add to only one existing study on the intergenerational risk associated with parental interpersonal problems [28], which found that parental interpersonal problems were associated with adolescent BPD features. This is the first study to suggest a relationship between maternal interpersonal problems and offspring attachment.…”
Section: Discussionsupporting
confidence: 89%
“…Regarding clinical applications of these findings, we focus on a population for which interpersonal problems are highly relevant: parents with personality pathology. While we did not directly measure parental personality pathology, there is theoretical and empirical support suggesting that interpersonal problems on the IPC aligns with severity of personality dysfunction as defined by the alternative model of personality disorders (AMPD; [28,75]). Our results provide important new contributions to the literature on parents with personality disorders, which has focused primarily on borderline personality disorder (BPD) and has found that maternal BPD is associated with disrupted attachment in offspring [23,24,35,36].…”
Section: Discussionmentioning
confidence: 99%
“…BOR had correlations ≥.60 with several other PAI scales—including Aggression, Anxiety, Anxiety-Related Disorders, Depression, Paranoia, Schizophrenia, and Stress—in both samples. In addition, studies in our database reported that the PAI-BOR scale correlated .66 (Zalewski et al, 2020) and .69 (Dixon-Gordon & Laws, 2021) with depressive symptoms, and .60 with an indicator of internalizing psychopathology (Kerr et al, 2021).…”
Section: Comorbiditymentioning
confidence: 78%
“…Increasing evidence suggests at this point that in the earliest stage broad vulnerabilities can be described at the trait level (Beauchaine et al, 2017) around which personality dysfunction with regard to self and interpersonal experiences further develops over time (Kerr et al, 2021;Vanwoerden et al, 2021), with fast developmental processes and increasing discriminative value of early traits toward maladaptive outcomes throughout adolescence (De Clercq et al, 2017). However, one issue that remains pertinent in the search for the most accurate assessment relates to the core feature of stability and change of personality pathology (Tackett et al, 2009), which is particularly the case for borderline-related traits.…”
mentioning
confidence: 99%